TRAINING AND SUPPORT, OBSTACLES, AND LIBRARY IMPACTS ON ELEARNING ACTIVITIES. - Dempsey, J. V.; Fisher, S. F.; Wright, D. E.; Anderton, E. K. (College Student Journal)
Using the Internet for courses, as an enhancement to the traditional class, or for a fully online course in higher education has become routine over the last several years. Less common are empirically-based studies of its implementation. This study concentrated on areas of faculty and student training and support, challenges, and online use of library resources experienced by both faculty and students. Data was collected from six groups comprised of faculty (n=140) and students (n=707) participating in entirely online courses, web-enhanced courses, and courses taught entirely in a traditional classroom format across all disciplines of a southern US university. Results of the study were categorized into the areas mentioned above based on the strength of response. Faculty reported training to be particularly important and the increased time spent developing and teaching online courses as a major obstacle. Surprisingly, both faculty and students involved with traditional courses reported heavier usage of online library resources than faculty and students involved with fully-online courses.